PREVALENSI CACING SALURAN PENCERNAAN PADA KAMBING PERANAKAN ETAWA (PE) DI KELOMPOK TANI KECAMATAN GEDONG TATAAN KABUPATEN PESAWARAN LAMPUNG - Mulyadi, Taufik; Siswanto, Siswanto; Hartono, Madi (Jurnal Riset dan Inovasi Peternakan, 2018)
Research held in Peranakan Etawa (PE) Goat's Farmers Group of Gedong Tataan, Pesawaran Regency Lampung on July--August 2017. It is purpose to know prevalence of Gastrointestinal Worms at Peranakan Etawa (PE) Goat in Farmers Group of Gedong Tataan, Pesawaran Regency Lampung. The research using the survey method. Sampling is done by proportional method. The number of samples obtained is 77 samples. Data was analyzed by descriptive analyzed. Faecal samples examination checked with Mc. Master and Sedimentation test at Balai Veteriner. The result showed that the prevalence of gastrointestinal worms at PE goat who maintained by farmer groups in Gedong Tataan about 85.71%. There are 66 PE goats positively infested gastrointestinal worms. Prevalence is the total number of individuals or percentage of the population infected with a disease in an area over a period of time. The highest prevalence is found in PE goat which is maintained by Sehati Jaya Farmer Group that is 88.24% , while the lowest prevalence is found in PE goat which is maintained by KWT Sekar Mawar farmer that is 72.73%. The type of Gastrointestinal worms that found in PE goats which is maintained by farmer groups in Gedong Tataan came from the nematode class (Haemonchus sp., Oesophagostomum sp., Mecistocirrus sp., Syngamus sp., Trichostrongylus sp., Bunostomum sp., Strongyloides sp., Ostertagia sp , Capilaria sp., and Trichuris sp.), cestoda class (Moniezia sp.), and trematoda class (Paramphistomum sp.). Keywords: Gastrointestinal worms, Prevalence, Peranakan Etawa Goat.